Aplikasi Metode HIRARC dan Domino untuk Risk Assessment Keselamatan dan Kesehatan Kerja (K3) Proyek Pengendali Banjir Tukad Unda di Wilayah Kabupaten Klungkung - Ni Putu Indah Yuliana; Fransiska Moi; Ni Kadek Sri Ebtha Yuni (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2023)
Tukad Unda flood control project has complex work that poses occupational health and safety risks. The objectives of the study identify occupational safety and health risks, determine the value of risks, determine the causes of the Tinggiest risks and determine risk control. The research used the Hazard Identification Risk Assessment and Risk Control and Domino methods. The study showed 101 hazard identifications with 34 sources of danger, of which the extreme category was 31 risks, the Tinggi category was 46 risks and the Sedang category was 24 risks. Factors causing the Tinggiest risk are the lack of attention of workers during safety talks, lack of optimizing standard operating procedures for work procedures, the absence of regular inspection of work equipment and areas, the lack of structured work position arrangements and safety signs, workers not wearing personal protective equipment, workers lacking discipline in the application of personal protective equipment , workers are less concerned about the work area environment, workers are less vigilant, workers joke when doing work and do not apply work instructions. Risk control with meeting box tools, arranging work positions and tools, work permits and personal protective equipment.